The fourth estate at the fourth wall : newspapers on stage in July Monarchy France - Hollinshead-Strick, Cary (Northwestern University Press, 2019)
"New media are often greeted with suspicion by older media. When the commercial press arrived in France, in 1836, popular theater critiqued its corruption, its diluted politics, and its tendency to orient its content towards the lowest common denominator. July Monarchy plays, which provided affordable entertainment to a broader section of the public than even new newspapers did, constitute a large, nearly untapped reservoir of commentary on the arrival of the forty-franc press. Vaudevilles and comedies ask whether journalism that benefits from advertisement can be unbiased. Dramas explore whether the threat of spreading fake news is an acceptable way for journalists to exercise their influence. Both plays and novels suggest that media that claim to enlighten can sometimes obscure public access to information. Balzac's interventions in this media sphere reveal his utopian views on print technology. Nerval's and Pyat's demonstrate the nefarious impact that corrupt theater critics could have on authors and on the public alike. Scholars of press and media studies, French literature, theater, and nineteenth-century literature more generally will find this book a valuable introduction to a cross-genre debate about press publicity that remains surprisingly resonant today"--Provided by publisher